2012
DOI: 10.3402/pba.v2i0.17293
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone, inflammation and aging

Abstract: Mutant animals characterized by extended longevity provide valuable tools to study the mechanisms of aging. Growth hormone and insulin-like growth factor-1 (IGF-1) constitute one of the well-established pathways involved in the regulation of aging and lifespan. Ames and Snell dwarf mice characterized by GH deficiency as well as growth hormone receptor/growth hormone binding protein knockout (GHRKO) mice characterized by GH resistance live significantly longer than genetically normal animals. During normal agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 50 publications
(65 reference statements)
5
64
0
1
Order By: Relevance
“…The rate of ageing varies across species and is genetically based (Bowen and Atwood 2004). In humans, the ageing phenotype is characterized by hearing loss, visual impairment (Roth 2015), wrinkles and other skin conditions (Yosipovitch et al 2007), a steady decline in many cognitive processes (Deary et al 2009), a decrease in sex and growth hormones (Masternak and Bartke 2012), and increased inflammation (Starr et al 2009). The elderly are the fastest-growing segment of the population, and it is estimated that by 2050, there will be two billion people over the age 60 and they will outnumber the children (Glatt et al 2007).…”
Section: Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of ageing varies across species and is genetically based (Bowen and Atwood 2004). In humans, the ageing phenotype is characterized by hearing loss, visual impairment (Roth 2015), wrinkles and other skin conditions (Yosipovitch et al 2007), a steady decline in many cognitive processes (Deary et al 2009), a decrease in sex and growth hormones (Masternak and Bartke 2012), and increased inflammation (Starr et al 2009). The elderly are the fastest-growing segment of the population, and it is estimated that by 2050, there will be two billion people over the age 60 and they will outnumber the children (Glatt et al 2007).…”
Section: Ageingmentioning
confidence: 99%
“…Reduced growth hormone (GH, called also somatotropin) level emerges as biomarker of ageing as well as a suspected causal factor in various symptoms and functional deficits associated with the ageing process (Masternak and Bartke 2012). The hormones, which have increasing levels at puberty, such as GH, strongly affect body composition and strength.…”
Section: Growth Hormonementioning
confidence: 99%
“…(7) One study showed weight increase and hypertrophy of white adipose tissue (WAT) with age in the internal organs and subcutaneous tissues. (29) Secretion of the pro-inflammatory cytokines TNF-α and IL-6 by adipocytes and accumulation of macrophages in adipose tissue causes a chronic systemic inflammatory condition (inflammaging), (30) resulting in DNA damage and degeneration in various body tissues. Other studies showed that aging increases foci of DNA damage in various organs, such as the lungs, liver, and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma IL-6 level and insulin sensitivity relationship is very remarkable and there is a very strong controversial connection between them (Kern et al 2001). It is suggested that the shift of the secretory profile of adipose tissue from pro-to anti-inflammatory importantly contributes to improved insulin sensitivity-reduced rate of aging and extended longevity in mice lacking GH signals (Masternak and Bartke 2012). It is said that the exercise program applied along with low-calorie diet could decrease the inflammation rate by reducing the plasma levels of some cytokines like IL-6, CRP, and TNF-α (Brunn et al 2006).…”
Section: Discussionmentioning
confidence: 99%